2018
DOI: 10.1021/acs.biochem.8b00290
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Use of TurboLuc Luciferase as a Reporter for High-Throughput Assays

Abstract: Luciferase-based reporter assays are powerful tools for monitoring gene expression in cells because of their ultrasensitive detection capacity and wide dynamic range. Here we describe the characterization and use of a luciferase reporter enzyme derived from the marine copepod Metridia luciferase family, referred to as TurboLuc luciferase (TurboLuc). To develop TurboLuc, the wild-type luciferase was modified to decrease its size, increase brightness, slow luminescent signal decay, and provide for efficient intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…2) with a molecular mass of 9-10 kDa corresponding to GpLuc tandem repeats was identified. Complementation of the N-and C-terminal fragments of GpLuc resulted in reconstitution of only 10% of the initial activity, but this value was comparable to or exceeded the specific activity of intact RLuc and FLuc (21,55). In contrast to the results of the study (27), the fragments separately did not exhibit any bioluminescent activity and revealed reversible complementation, enabling quantitative measurement of dynamic and transient protein-protein interactions.…”
Section: Protein-fragment Complementation Assaymentioning
confidence: 72%
See 2 more Smart Citations
“…2) with a molecular mass of 9-10 kDa corresponding to GpLuc tandem repeats was identified. Complementation of the N-and C-terminal fragments of GpLuc resulted in reconstitution of only 10% of the initial activity, but this value was comparable to or exceeded the specific activity of intact RLuc and FLuc (21,55). In contrast to the results of the study (27), the fragments separately did not exhibit any bioluminescent activity and revealed reversible complementation, enabling quantitative measurement of dynamic and transient protein-protein interactions.…”
Section: Protein-fragment Complementation Assaymentioning
confidence: 72%
“…), was constructed on the base of conservative catalytic parts of MpLuc1 from Metridia pacifica and MLuc164 from M. longa . In terms of activity, TurboLuc was comparable with wt Gaussia luciferase but had a 10‐nm red shift as compared to 470‐nm peak of wt GpLuc at the same assay conditions .…”
Section: Improvement Of Reporter Properties By Mutagenesismentioning
confidence: 88%
See 1 more Smart Citation
“…Some compounds increase enzymatic activity, while others decrease it. The TurboLuc system reported by Audi et al is somewhat smaller in molecular weight (16 kDa) than NanoLuc [73]. Compared with NanoLuc Protein-Protein Interaction Assays Using Split-NanoLuc DOI: http://dx.doi.org /10.5772/intechopen.86122 and Firefly luciferase, the activity of TurboLuc was less affected by low-molecular weight compounds.…”
Section: Discussionmentioning
confidence: 98%
“…uHTS in 1536-well microtiter plate (1536w-MTP) formats can enable assay volumes of less than 5 μL and a throughput of more than a 100,000 assays per day [ 36 ]. Auld et al [ 37 ] screened two low molecular weight compound libraries (44,000 compounds) and a purified natural products library (2583 compounds) to describe the inhibitor profile of purified enzyme, TurboLuc, and also showed the use of this reporter enzyme in cell-based assays employing uHTS in 1536w-MTP. Norcliffe et al [ 38 ] adopted an auxotrophic yeast-based uHTS approach for inhibitors of the Leishmania enzyme (inositol phosphorylceramide synthase).…”
Section: Well Plate Setupsmentioning
confidence: 99%